EFFECTIVE ONLINE LEARNING METHODS FOR LEARNING FOREIGN LANGUAGES (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the realm of effective online learning methods designed to facilitate the acquisition of foreign languages. The discussion encompasses a diverse array of digital tools and platforms, emphasizing their transformative impact on language education. The highlighted methods include Interactive Communication Platforms, which enable real-time engagement with native speakers, creating dynamic and culturally rich language learning experiences.